Soil Remediation Applications of Nanotechnology - Risky Ayu Kristanti; Rachael Mei Yen Liong; Tony Hadibarata (Tecno Scientifica Publishing, 2021)
With the growth of urbanization, the anthropogenic activities have increased and thus increase occurrence of soil contaminants. In order to eliminate the contaminants in soil environment, the application of nanotechnology for soil remediation has become a great concern in the world. This review will discuss about the fate of contaminants in soil environment; the mechanisms of nanotechnology with various types of nanomaterials for the soil remediation; the advantages and disadvantage of nanomaterials towards the terrestrial organisms, human health as well as the soil environment; and the challenges of using nanotechnology for soil remediation.